Acid‐Catalyzed Synthesis of α‐Trifluoromethylthiolated Carbonyl Compounds. Issue 21 (22nd June 2015) - Alazet, Sébastien; Ismalaj, Ermal; Glenadel, Quentin; Le Bars, Didier; Billard, Thierry
Abstract: The α‐trifluoromethylthiolation of carbonyl compounds in soft acidic conditions has been developed. With this method only mono‐trifluoromethylthiolation was selectively observed. Base‐sensitive ketones can then be trifluoromethylthiolated. More sensitive aldehydes are also trifluoromethylthiolated under these conditions with good yields. This work provides a new route towards the synthesis of various valuable trifluoromethylthiolated molecules. Abstract : One reagent, two possibilities: Complementary to previously described base‐catalyzed reactions, α‐trifluoromethylthiolations of carbonyl compounds were realized in soft acidic conditions with a second generation trifluoromethanesulfenamide. Different selectivities were then observed. With this new strategy, all types of CF3 S‐carbonyl compounds can be synthesized by starting from the same reagent.